2016
DOI: 10.1080/2162402x.2016.1257452
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-infiltrating lymphocyte composition, organization and PD-1/ PD-L1 expression are linked in breast cancer

Abstract: The clinical relevance of tumor-infiltrating lymphocytes (TIL) in breast cancer (BC) has been clearly established by their demonstrated correlation with long-term positive outcomes. Nevertheless, the relationship between protective immunity, observed in some patients, and critical features of the infiltrate remains unresolved. This study examined TIL density, composition and organization together with PD-1 and PD-L1 expression in freshly collected and paraffin-embedded tissues from 125 patients with invasive p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
188
6
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 191 publications
(229 citation statements)
references
References 60 publications
21
188
6
1
Order By: Relevance
“…However, fresh tissue is required and no information is provided on the distribution or organization of the immune infiltrate or relationship to other microenvironmental structures. Nevertheless, recent study of TILs in invasive breast carcinoma found a significant positive correlation between fresh tumor tissue analyzed by flow cytometry and IHC stained sections scored by a pathologist [26]. Messenger RNA (mRNA) profiling of tumor tissue can detect “immune gene signatures”, using the level of expression of immune related genes to describe the composition and functional status of the immune infiltrate [27].…”
Section: The Host Immune Responsementioning
confidence: 99%
“…However, fresh tissue is required and no information is provided on the distribution or organization of the immune infiltrate or relationship to other microenvironmental structures. Nevertheless, recent study of TILs in invasive breast carcinoma found a significant positive correlation between fresh tumor tissue analyzed by flow cytometry and IHC stained sections scored by a pathologist [26]. Messenger RNA (mRNA) profiling of tumor tissue can detect “immune gene signatures”, using the level of expression of immune related genes to describe the composition and functional status of the immune infiltrate [27].…”
Section: The Host Immune Responsementioning
confidence: 99%
“…111 123 Noteworthy, spontaneous antitumour immune infiltration was shown to be higher in primary tumours with respect to matched metastases (reviewed in Solinas et al 124 ), suggesting that administration of ICB in the early setting might be more effective than in the advanced setting. Novel immune strategies aiming at inducing (ie, vaccines, adoptive T cell therapy or ICB combinations including CT and RT) or boosting a pre-existing not-sufficient immune response 44 should be developed in BC to increase the benefit from ICB.…”
Section: Future Challenges Of Immune Checkpoint Blockade In Breast Camentioning
confidence: 99%
“…In BC, PD-L1 expression correlates with hormone receptor negativity, higher histological grade, proliferation and TIL infiltration. 44 As such, PD-1/PD-L1 have been evaluated as therapeutic targets in a variety of trials, of which results are discussed below.…”
Section: Introductionmentioning
confidence: 99%
“…+ tumor-infiltrating lymphocytes (TIL) in human BC specifically expressing CXCL13 (5,25), but curiously, the majority were CXCR5 -cells located both in TLS containing a GC (TLS/GC) and the tumor bed. CXCR5 -CXCL13 + CD4 + T cells have also been detected in rheumatoid synovitis from patients but were not viewed as T FH cells because of their CXCR5 negativity (26,27).…”
Section: Cd3 + Cd4mentioning
confidence: 99%